Insiders, Outsiders, and the Underground Economy - Dan Anderberg (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper considers whether labour market rigidities lead to more underground economic activities. This is suggested by aggregate cross-country data which show that underground economic activities are more strongly correlated with a commonly used index of employment protection than with effective tax rates. A simple theoretical model is constructed to support this finding. The model, contrary to many models of equilibrium unemployment in the literature, also has the feature that a rise in a proportional tax affects employment (in addition to underground economic activities).
Keywords: 330